Complex thinking through a Transition Design-guided Ideathon: testing an AI platform on the topic of sharing economy - Sanabria-Z, Jorge; Castillo-Martínez, Isolda Margarita; González-Pérez, Laura Icela; Ramírez-Montoya, María Soledad (Frontiers in Education, 2023)
Rationale: The development of the complex thinking meta-competency in the education of university students potentially promotes high capacities, and artificial intelligence (AI) might work as a supporting structure. Objective: This study aimed to integrate the flow of proof-of-concept activities into the design of an online AI platform to assess the development of complex thinking competency in higher education students. Method: The Transition Design method was used within an Ideathon event supported by an AI platform to provide students with a Sharing Economy challenge. A total of 31 university students from five university campuses in Mexico synchronously participated. An instrument was applied in the pre-test and post-test phases to explore the complex thinking meta-competency and its sub-competencies of critical, scientific, systemic, and innovative thinking. Results: Two hypotheses were tested, both of which turned out to be true: a) the functioning of the constructed learning situation and b) the model of the learning situation. Conclusion: These findings may be of value to scientific and academic communities and social and business organizations interested in developing high capacities of complex thinking and educational innovations using digital platforms.